High School Blugold Beginnings Program : an Investigation of Program Impact - Nygaard, Abigail; Rojas, Giney; Yang, Kalia; Yang, Cindy (My University, 2012)
The Blugold Beginnings: College and Career Readiness High School Program works with local schools to provide a comprehensive college connection for high school students. The purpose of this study was to investigate whether students in the program tend to significantly increase their knowledge about post-secondary education over the course of participating in the Blugold Beginnings: College and Career Readiness Program, and to assess whether this increased awareness coincides with increased feelings of comfort and confidence regarding higher education.
Colo poster with text and graphs.
Keywords: High school students--Education, higher; Blugold Beginnings (Eau Claire, Wis.); College preparation programs--Wisconsin--Eau Claire--Longitudinal studies; Posters